Analysis Of Bilingualism In 5 Year Olds In Pasir Utama Village, Rambah Hilir District Rokan Hulu Regency, Riau Province - Irawati, Irawati; Lubis, Anita Angraini (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research is motivated by the use of two languages by 5-year-old children, namely Indonesian and Javanese in their daily lives. A 5-year-old child with a language acquisition process that can master and use two languages well, namely Indonesian and Javanese, located in Pasir Utama Village, Rambah Hilir District, Rokan Hulu Regency, Riau Province. The study aims to analyze forms of bilingualism in 5-year-old children in Pasir Utama Village, Rambah Hilir District, Rokan Hulu Regency, Riau Province using qualitative research methods. The theories that support this research consist of sociolinguistics, bilingualism, and children's social development. This type of research is qualitative research, which is research that is directly carried out in the field. The data collections techniques used in this study are observation, interviews, and documentation. The focus of this study is to determine the form of bilingualism in 5-year-old children in the use of language in daily life. The data analysis technique used to obtain the result of this research is the Milles Huberman data analysis technique which consists of data collection, data reduction, data presentation, and conclusion drawn. The result of this stud show that there are 10 data obtained by the researcher from 2 5-year-old research subjects, including the form of coordinated bilingualism and the from of pluralistic bilingualism. In conclusion, there are 10 forms of data speeches in the form of coordinated bilingualism and 3 data speeches in the form of plural bilingualism, so that judjing from allthe data obtained by the researcher as 5-year-old children as the subject of the research, the researcher is said to be 100% bilingual with a percentage of 70% coordinated bilingualism and 30% plural bilingualism. There are several factors that cause bilingualism in-5-year-olds, namely the family environment, the living environment and interaction with peers.